PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT KARYA INDAH PERMATA TANJUNG REDEB: PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT KARYA INDAH PERMATA TANJUNG REDEB - Edwar Ready (ECO-BUILD, 2022)
This study aims to explain whether the motivation and compensation variables have a significant effect on employee performance at PT. Karya Indah Permata and to find out which variable has the dominant influence between the two variables of Motivation and Compensation on employee performance at PT Karya Indah Permata. This study raises the issue of the influence of motivation and compensation on employee performance. The respondents used were 78 employees of PT Karya Indah Permata in Berau. Respondents who have filled out the questionnaire will then be identified based on gender, age, length of work, education, and salary. This identification was carried out to determine the general characteristics of the research respondents. The results of testing the hypothesis (H1) have proven that there is an influence between motivation on employee performance. Through the results of the calculations that have been carried out, it is obtained that the t value is 0.085 with a significance level of 0.000 > 0.05, thus the first hypothesis is accepted/according. The results of testing the hypothesis (H2) have proven that there is an influence between compensation on employee performance. Through the results of the calculations that have been carried out, it is obtained that the t value is 0.995 with a significance level of 0.000 > 0.05, thus the second hypothesis is accepted/according The results of testing the hypothesis (H3) have proven that there is an influence between motivation and compensation on employee performance. Through the results of the calculations that have been carried out, it is obtained that the calculated f value is 1140.595 with a significance level of 0.000 > 0.05, thus the third hypothesis is accepted/according.